2022
DOI: 10.1021/acsanm.2c02910
|View full text |Cite
|
Sign up to set email alerts
|

Ordered GaN Nanorod Arrays for Self-Powered Photoelectrochemical Ultraviolet Photodetectors

Abstract: Self-powered ultraviolet (UV) photodetectors have great application prospects in the fields of UV astronomy, environmental monitoring, and space communication. In particular, the emerging photoelectrochemical photodetectors (PEC PDs) without external bias, high sensitivity, and environmental sensitivity have attracted extensive attention. Herein, self-powered PEC PDs were designed and constructed by using highly ordered GaN nanorod arrays (NRAs) as photoelectrodes. Without external bias, PEC PDs with NRA struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The photodetection performance for OV-Bi 4 O 5 I 2 PEC-type photodetector was much better than those of other bismuth-based PEC-type photodetectors and comparable to the well-investigated inorganic materials-based PEC-type photodetectors (Figure 4g and Table 1). [3,5,11,[44][45][46][47][48][49][50][51][52][53][54][55][56][57] These results strongly suggested that OV-Bi 4 O 5 I 2 PEC-type photodetector is a promis-ing nanodevice suitable for various applications, like optical imaging, optical communication, and biomedical detection.…”
Section: Resultsmentioning
confidence: 99%
“…The photodetection performance for OV-Bi 4 O 5 I 2 PEC-type photodetector was much better than those of other bismuth-based PEC-type photodetectors and comparable to the well-investigated inorganic materials-based PEC-type photodetectors (Figure 4g and Table 1). [3,5,11,[44][45][46][47][48][49][50][51][52][53][54][55][56][57] These results strongly suggested that OV-Bi 4 O 5 I 2 PEC-type photodetector is a promis-ing nanodevice suitable for various applications, like optical imaging, optical communication, and biomedical detection.…”
Section: Resultsmentioning
confidence: 99%
“…TiN 52 is used as a refractory plasmonic material due to its excellent properties. In contrast, GaN 56 is used as a semiconductor with a 3.4 eV band gap 57 to support a variety of applications that involve hot electron 58 injection from a plasmonic metal into a semiconductor to harvest broad-range photons that would otherwise go unutilized due to the semiconductor's wide band gap. TiN and GaN are materials with high chemical stability and resistance to corrosion, making them suitable for harsh environments.…”
Section: Introductionmentioning
confidence: 99%
“…UV PDs are considered essential components in a wide range of applications, including environmental monitoring, flame detection, GPS and telecommunications, military and strategic purposes, and chemical and biological reactions. [1][2][3][4][5] Additionally, UV photodetectors are gaining high importance in the rapidly expanding fields of the Internet of Things (IoT) and smart wearables. [6,7] In order to operate in extreme conditions, the active material of UV PDs should be able to withstand harsh environments and operate with high power efficiency.…”
Section: Introductionmentioning
confidence: 99%